PENDIDIKAN IBU BERSALIN DAN DUKUNGAN KELUARGA DALAM MEMANFAATKAN FASILITAS PERSALINAN DI PONED PUSKESMAS WANAYASA KABUPATEN PURWAKARTA - Pupung Rahayu; Ani Yunaningsih (Holistik Manajemen: Jurnal Manajemen, 2021)
This study aims to determine whether education and family support affect the decision of the mother to utilize birth facilities in the PONED. This research is a quantitative research using questionnaires. Sampling technique in this research using Probability Sampling with technique type Quota sampling. The number of samples is 90 respondents. The dependent variable is the utilization of birthing facilities in PONED whereas education and family support as independent variables. Data analysis was done gradually including univariate, bivariate (chi- square) and multivariate (logistic regression). The average research respondents were about 29.9 years old, with a minimum age of 21 and a maximum age of 45 years. Most of the elementary education is 58 respondents (64.4%). From the result of bivariate test there is significant influence between education to utilization of PONED facility and from variable family support, statistical test results a very significant influence between family support and utilization of PONED. From the multivariate test it was found that education and family support together had an effect on the utilization of birthing facilities at PONED at the Wanayasa Puskesmas.